2020
DOI: 10.1021/acs.jafc.9b07505
|View full text |Cite
|
Sign up to set email alerts
|

Odor Perception Interactions between Free Monoterpene Isomers and Wine Composition of Pinot Gris Wines

Abstract: Monoterpenes are aromatic compounds that are of great interest to wine as they are related to the quality of varietal wines. However, there is little information available about the impact of monoterpenes on wine odor perception at sub-or perithreshold concentrations. The aim of this study was to investigate odor perception of monoterpene isomers in Pinot Gris wine and determine compositional matrix effects. Monoterpene isomers were quantitated in 46 Pinot Gris wines using headspace solid-phase microextraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 44 publications
3
45
0
Order By: Relevance
“…This was previously observed in a study on the aroma of Muscat, in which the authors showed that a monoterpene mixture can significantly lower the sensory threshold of each singular compound when taken separately (Ribéreau-Gayon et al, 1975). Moreover, a recent study on Pinot gris showed that the non-volatile wine composition strongly increased the volatility of the free monoterpenes (Tomasino et al, 2020). Finally, diendiol (I) was the most concentrated compound that we observed in the D wine of Tocai Friulano 2012.…”
Section: Impact Of Water Deficit On Wine Vocs In Tocai Friulano and Msupporting
confidence: 81%
See 1 more Smart Citation
“…This was previously observed in a study on the aroma of Muscat, in which the authors showed that a monoterpene mixture can significantly lower the sensory threshold of each singular compound when taken separately (Ribéreau-Gayon et al, 1975). Moreover, a recent study on Pinot gris showed that the non-volatile wine composition strongly increased the volatility of the free monoterpenes (Tomasino et al, 2020). Finally, diendiol (I) was the most concentrated compound that we observed in the D wine of Tocai Friulano 2012.…”
Section: Impact Of Water Deficit On Wine Vocs In Tocai Friulano and Msupporting
confidence: 81%
“…This can explain the low olfactive scores received in the Tocai Friulano sensory test, because (i) the free aromatic compounds of the skins were probably lost during the separation of solids before the must fermentation, and (ii) the majority of aromatic compounds we measured were in the odourless form (glycosidicallybound). Therefore, in order to thoroughly benefit from the aromatic properties of white grape grown under water deficit conditions, it would be useful to extend skin contact time or perform limited skin maceration during grape berry crushing, and/ or to enzymatically hydrolyse the vast reservoir of glycosidically-bound monoterpenes by using adhoc strain yeast (van Wyk et al, 2019). However, up to now, the results that have been reported are debatable (reviewed in Hjelmeland and Ebeler, (2014); for example, the use of enzymatic or acid hydrolysis may lead to unwanted release of compounds (off-aromas), or to a reduction in the efficacy of glucosidase since it has been shown that their activity is limited by increasing ethanol and glucose concentration.…”
Section: Wine Sensorial Analysis In Tocai Friulano and Merlotmentioning
confidence: 99%
“…The importance of quantifying free monoterpenes in the sub-threshold range was emphasised by [57]. Rather negative evaluation of free monoterpenes in connection with Pinot blanc typicity is interesting for several reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Bindon et al quantified isobutyl methoxypyrazine (IBMP), isopropyl methoxypyrazine (IPMP) and sec-butyl methoxypyrazine (SBMP) using IBMP-d3 as an internal standard. More recently, Tomasino et al [63] used the SIDA approach to quantify monoterpene isomers in forty-six Pinot Gris wines by HS-SPME multidimensional gas chromatography mass spectrometry. Dang et al [64] quantified volatile phenols using relative peak areas, i.e., the ratio between the peak area of the analyte and the one of the normalizing standard (d3-4-methylguaiacol).…”
Section: Standard Addition Methodsmentioning
confidence: 99%